2017
DOI: 10.1111/wrr.12591
|View full text |Cite
|
Sign up to set email alerts
|

Wnt and frizzled expression during regeneration of internal organs in the holothurian Eupentacta fraudatrix

Abstract: Several genes of the Wnt and Frizzled families in the holothurian Eupentacta fraudatrix are characterized, and the complete coding sequences of wntA, wnt4, wnt6, wnt16, frizzled1/2/7, frizzled4, and frizzled5/8 are obtained. The dynamics of expression of these genes during regeneration of internal organs after evisceration are studied. Evisceration and the associated damages supposedly induce the expression of wnt16 on third day after evisceration. Genes wntA, wnt4, wnt6, and frizzled1/2/7 up-regulate during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…schmeltzii . We found products of 10 out of the 12 wnts typical of holothurians [ 155 ]– wntA , wnt1-7 , wnt10 , wnt16 ( S1 Table ). Transcripts of wnt2 and wnt4 were found only in dividing individuals, whereas wnt1 and wnt7 were revealed both in intact and in dividing holothurians ( Table 3 , S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…schmeltzii . We found products of 10 out of the 12 wnts typical of holothurians [ 155 ]– wntA , wnt1-7 , wnt10 , wnt16 ( S1 Table ). Transcripts of wnt2 and wnt4 were found only in dividing individuals, whereas wnt1 and wnt7 were revealed both in intact and in dividing holothurians ( Table 3 , S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is known that the Wnt signaling pathway plays an important role in regeneration in various animals [ 156 159 ]. Recently, it has been shown that some wnt genes are expressed during restoration of internal organs in holothurians [ 155 , 160 , 161 ]. In this regard, it can be assumed that this signaling pathway, along with the transcription factors (see below), is involved in regulation of fission and/or preparation of holothurian tissues for subsequent regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…Some Wnt genes (eg., Wnt6 and WntA ) have been identified involved in the intestinal regeneration of sea cucumbers (Sun et al, 2013; Li et al, 2017). Other genes, including Wnt4, Fz1/2/7 , and Fz5/8 , were identified upregulated during 5–10 days after evisceration and might participate in regulation of tissue and organ formation during intestinal regeneration (Girich et al, 2017). However, in this study, Wnt7, Fz7 , and Dvl were the only three genes that identified to be positively selected in the Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, after 14 and 20 dpe, changes in the expression of all Wnt and frizzled genes are minimal. It is worth mentioning that the dynamics of frizzled1/2/7 differ between E. fraudatrix and A. japonicus [167,206]. This may be explained by different functions of pathways which activated through the receptor Frizzled1/2/7.…”
Section: Wnt Signaling Pathwaymentioning
confidence: 97%
“…The Wnt signaling pathway is activated in the regeneration of the organs of the anterior part of the body in E. fraudatrix (AB and the anterior part of the gut). Gene transcripts of four ligands (wntA, wnt4, wnt6, and wnt16) and three receptors (frizzled1/2/7, frizzled4, and frizzled5/8) have been identified in the AB and gut anlagen [206]. All of them exhibit different expression dynamics.…”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%